Safety of machinery. Electro-sensitive protective equipment. Particular requirements for equipment using vision based protective devices (VBPD). Additional requirements when using reference pattern techniques (VBPDPP) Part 4-2, (28th April 2023) - British Standards Institution,
No abstract available